PEMBERDAYAAN KELOMPOK KESWADAYAAN MASYARAKAT (KKM) DALAM PEMETAAN AIR TANAH UNTUK MITIGASI KEKERINGAN DI DESA PASIRWARU, GARUT - Santoso, Budy; Wijatmoko, Bambang; Qonitatin, Salisa Syifaunajwa; Men, Liu Kin; Mahendra, Muhammad Akbar Putra; Rinaldy, Mochamad Indiana; Purnama, Ikhsan Milan (Jurnal Abdi Insani, 2025)
Pasirwaru Village, located in Garut Regency, is a hilly area that frequently experiences clean water shortages during the dry season. The community's dependence on water supply from the local government reflects the absence of a sustainable and independent water provision system. The lack of subsurface geological information also poses challenges in identifying groundwater sources. Therefore, a scientific approach is required to effectively and efficiently map groundwater potential. This community service program was carried out to enhance local capacity through training in the application of electrical resistivity methods for groundwater mapping. The method applied in this activity refers to the Participatory Action Research (PAR) approach, which encourages active involvement of the community from problem identification to technical training and data interpretation. The program was conducted in Pasirwaru Village, Blubur Limbangan Sub-district, involving the Community Self-Help Group as the main partner. The program yielded positive outcomes, as evidenced by the increased technical understanding of participants regarding geoelectrical methods and their ability to independently conduct field measurements. Five survey points indicated the presence of a potential aquifer at depths exceeding 70 meter, with resistivity values ranging from 28.42 to 53.23 Ohm.meter. These layers were interpreted as water-saturated tuffaceous sands with good permeability. Stakeholders, including local officials and residents, responded positively and expressed interest in replicating the program in nearby areas. This program has proven effective in achieving its objective of empowering the community through science-based knowledge transfer and generating foundational data to support sustainable drought mitigation strategies.